2016
DOI: 10.1111/1753-6405.12561
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Australian adolescents' sun‐protection behaviours: implications for health campaigns

Abstract: Objective: Protecting the skin from ultraviolet (UV) radiation is critical during adolescence to reduce the risk of developing skin cancer later in life, but adolescents tend to be less likely to engage in sun‐protective behaviours than adults. The present study examined changes and trends (2001/02–2011/12) in sun‐protection behaviours among adolescents living in Western Australia – a region with high levels of UV radiation. Methods: A cross‐sectional survey was conducted during 10 summers between 2001/02 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 53 publications
1
35
1
Order By: Relevance
“…The majority of our subjects spent time driving between 6.00-10.00 hours in the morning and 14.00-18.00 hours in the afternoon, during which UV-B radiation is lower. 40 A 5-year study from 2007 to 2012 of adults' sun-protective behavior showed an increasing trend of sunscreen use, but other protection means remained stable. One important contributing factor is a cultural preference for tanned skin color in Caucasians while Asians prefer a fair complexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of our subjects spent time driving between 6.00-10.00 hours in the morning and 14.00-18.00 hours in the afternoon, during which UV-B radiation is lower. 40 A 5-year study from 2007 to 2012 of adults' sun-protective behavior showed an increasing trend of sunscreen use, but other protection means remained stable. One important contributing factor is a cultural preference for tanned skin color in Caucasians while Asians prefer a fair complexion.…”
Section: Discussionmentioning
confidence: 99%
“…A 10-year study from 2001 to 2012 of Australian adolescents' sun-protective behavior revealed a significantly decreasing trend of using a hat, unchanged trends of using sunscreen and protective clothing (usually and always in 66% and 56% of the study population, respectively), but an increasing trend of staying inside (usually and always in 45% of the participants). 40 A 5-year study from 2007 to 2012 of adults' sun-protective behavior showed an increasing trend of sunscreen use, but other protection means remained stable. 41 A study of Canadian outdoor workers found that just over half always or often protected themselves by covering their head (58%), wearing protective clothing (56%) or wearing sunglasses (54%), and only 29% used sunscreen.…”
Section: Discussionmentioning
confidence: 99%
“…Wearing a hat as a protective measure experienced a decline in popularity even among Australian adolescents. 37 According to our results, Belgrade high school students do wear sunglassesone-third always, and as much as 94.35% at least sometimes. When Greek and Turkish adolescents were asked the same question (possible answers were yes or no), 25.5% of Greek 17 and 44% of Turkish students 36 answered affirmatively.…”
Section: Discussionmentioning
confidence: 58%
“…Three quarters of Belgrade adolescents who participated (75.77%) yet denied suffering severe sunburns accompanied by pain, redness and blisters; only every seventh student suffered these (14%).As for wearing a hat/cap during summertime, only 3.1% of students wear it always and additional 8.4% often; in similar studies, the answer to the same question was ‘always’ for half of Greek and Turkish interviewees. Wearing a hat as a protective measure experienced a decline in popularity even among Australian adolescents . According to our results, Belgrade high school students do wear sunglasses – one‐third always, and as much as 94.35% at least sometimes.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation